New Zealand household purchases of sugar-sweetened, artificially sweetened, and unsweetened beverages: 2015-2019 - Helen Eyles; Sah Dodd; Kelly K Garton; Yannan Jiang; Teresa Gontijo de Castro (Cambridge University Press, 2024)
Abstract Objective: To assess annual household purchases of sugar-sweetened beverages (SSBs), artificially sweetened beverages (AFSBs), and unsweetened beverages (USBs) by household composition and income, and over time. Design: Observational cohort study using beverage purchasing data linked to a supermarket database. ANOVA was used to compare total household purchase volumes (L) and the contribution of beverages purchased by category, household composition (size), household income (four categories from New Zealand (NZ) < $30 000 to > $90 000), and over time (trend from 2015 to 2019). Setting: Aotearoa NZ. Participants: ∼1800 households in the NielsenIQ Homescan® market research panel. Results: In 2019, the mean (sd) annual household purchase volume and relative contribution to total beverage volume of SSBs were 72·3 (93·0) L and 33 %, respectively. Corresponding values for AFSBs were 32·5 (79·3) L (15 %), and USBs were 112·5 (100·9) L (52 %). Larger households purchased more of all beverage types except AFSBs. Total purchases were similar by income, but households earning < $NZ 30 000 purchased fewer AFSBs and USBs (but not SSBs) than households earning > $NZ 90 000. Total and USB purchases were unchanged over time, but SSBs dropped by 5·9 L (P-trend = 0·04), and AFSBs increased by 5·3 L (P-trend = 0·00). Conclusions: USBs contributed the most to household beverage purchases. Total purchases were higher for larger households and similar by income, including for SSBs. The reduction over time was too small for health benefits. Findings support policies and interventions to reduce SSB consumption and highlight the importance of focusing on equitable outcomes.